Association Between C-Reactive Protein Levels and Glycemic Control Markers in Type 2 Diabetes Mellitus Patients (Derna Academy Journal for Applied Sciences, 2025)
Background: Systemic inflammation is a key pathophysiological feature of Type 2 Diabetes Mellitus (T2DM). C-reactive protein (CRP), a sensitive marker of inflammation, has been linked to T2DM risk factors, but its direct association with glycemic control markers remains inconsistent in the literature. Objective: This study aimed to investigate the association between CRP status and glycemic control as measured by fasting blood sugar (FBs) and glycated hemoglobin (HbA1c) in patients with T2DM. A secondary objective was to explore the relationship between CRP and various demographic, hematological, and lifestyle characteristics. Methods: A cross-sectional study was conducted on 119 patients diagnosed with T2DM. Participants were categorized as either CRP-positive or CRP-negative based on laboratory analysis. Data on demographics, hematological indices, iron status, and lifestyle factors were collected. Statistical analyses were performed to compare glycemic markers and other variables between the two CRP groups. Results: Of the 119 participants, 36 (30.3%) were CRP-positive and 83 (69.7%) were CRP-negative. The results demonstrated no statistically significant difference in FBs or HbA1c levels between the CRP-positive and CRP-negative groups. Furthermore, there was no significant association found between CRP status and demographic data (age, sex), hematological parameters, or self-reported lifestyle factors, including exercise habits, dietary patterns, and smoking status. Conclusion: In this patient cohort, CRP status alone was not a reliable indicator of glycemic control. The absence of a significant association suggests that the relationship between low-grade systemic inflammation, as measured by CRP, and glucose regulation in T2DM is complex and may be influenced by other unmeasured factors